Musculoskeletal Symptomatic Areas After Total Knee Replacement for Osteoarthritis. Issue 6 (1st August 2019) - Zhang, MaryAnn; Selzer, Faith; Losina, Elena; Collins, Jamie E.; Katz, Jeffrey N.
Abstract : Objective: The objective of this study was to measure cumulative incidence and incidence rate and identify factors associated with new musculoskeletal (MSK) symptomatic areas after total knee replacement (TKR) for osteoarthritis (OA). Methods: Using data from a randomized controlled trial of patients undergoing elective TKR for OA, we assessed for MSK symptomatic areas by region (neck, hands/wrists/arms/shoulders, back, hips, nonindex knee, and ankles/feet) at baseline (pre‐TKR), and at 3, 6, 12, 24, 36, and 48 months post‐TKR. Cumulative incidence and incidence rates were calculated for each region. Factors associated with incident MSK symptomatic areas were identified using generalized linear mixed models. Time to incident symptomatic area was assessed using Cox proportional hazards regression. Results: Among 293 subjects, the cumulative incidence of any new MSK symptomatic area over 4 years was 45%; the incidence rate was 19.2 per 100 person‐years. Body site–specific cumulative incidence and incidence rates were highest for nonindex knee and back. Predictors of incident MSK symptomatic areas included female sex (relative risk [RR] 1.64; 95% confidence interval [CI] 1.15‐2.34), body mass index of 35 or higher (RR 1.27; 95% CI 0.88‐1.85), Charlson Comorbidity Index 2 or more (RR 1.28; 95% CI 0.92‐1.78), baseline index knee Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain score greater than 40 (RR 1.39; 95% CI 0.99‐1.95), and anxiety/depression (measured by the five‐item Mental Health Index) (RR 1.70; 95% CI 1.20‐2.40). Conclusion: Incident MSK symptomatic areas occurred in roughly half of recipients of TKR in the 4 years after the operation. Further study is needed to examine the long‐term impact of MSK symptomatic areas on postoperative pain, function, and quality of life.